"If Someone Has It, I'm Gonna Hit It": Lessons Learned From Minnesota Teens About Vaping. Issue 6 (November 2022) - Less, Elyse Levine; Mady, Melissa; Beckman, Kara J.; Kingsbury, John H.
Youth e-cigarette use or "vaping" has increased substantially in the past few years, an escalation attributable to flavored "pod mod" e-cigarette devices that deliver higher levels of nicotine compared with free-base nicotine found in other types of e-cigarettes. Use rates, addiction, and harms are alarming as negative effects from nicotine on adolescent brain development are well documented, and e-cigarette use is predictive of cigarette smoking initiation. This qualitative study examined what drives the appeal of these products through 10 focus groups conducted in 2019 with 67 Minnesota high school students. Focus groups aimed to understand students' personal experiences and contextual factors that may contribute to current vaping trends and explore opportunities for improved prevention messaging. Study results revealed participants' divergent perceptions of tobacco products (i.e., vaping vs. e-cigarettes vs. cigarettes) and the benefits and harms of each product. Participants provided insights into why youth vape, describing vaping as an easily accessible coping method to help teens manage stress and anxiety. Peer normalization and invincibility beliefs about harms were also present. Participants generated ideas about prevention messaging, describing the ineffectiveness of prevention messages they currently receive, and expressing the need for accurate information about e-cigarette health risks presented in personalized, nonjudgmental contexts by people they know care about them. These results have clear implications for prevention initiatives and can be used to inform effective prevention strategies, messaging, programming, and policies, some of which are specific to e-cigarette prevention and others that align with the theory of positive youth development.